Do the Media Affect the Decisions of Policy Makers in Foreign Policy? - Ajjan, Mazen; Mehartaj Begum, Syed (Mediterranean Journal of Social Sciences, 2021)
On July 16th 2021, the U.S. newly elected President Joe Biden hosted Iraqi Prime Minister Mustafa Al-Kadhimi at the White House. The main topic was the future of the U.S. troops in Iraq. The controversial American invasion, after more than eighteen years, is again in focus. The American media in particular is allocating long hours of its live coverage in discussing this sensitive topic. This paper investigates the complex relationship between media and policymakers in the USA. The paper uses the invasion of Iraq in 2003 as a case study to address the question of the media’s influence on policy decision-making. By choosing two main media outlets in the "stalwart" on democracy: The New York Times and Fox News. The paper goes through a detailed account of how the Bush administration was able to impose their interpretation of the situation and how the media fostered misperceptions among the American public in one of the most world’s controversial crises. The conclusion from this analysis was that the media don’t affect policymaking. On the contrary, the American administration shaped the news coverage almost entirely. The Bush administration in 2003 was able to employ media to form its war agenda and spreading it to the public. Media, even in a democratic system, was unable to give counter argument or even a critical attitude towards Bush administration foreign policy. Received: 5 August 2021 / Accepted: 4 October 2021 / Published: 5 November 2021